The Effect of Customer Satisfaction on Loyalty of the Lembang Floating Market Tourism Area - Maris Agung Triandewo; Klemens Wedanaji Prasastyo; Alfira Azzahra (Journal of Business Social and Technology, 2023)
The main purpose of this study is to find out the influence of Customer Experiences on Customer Loyalty through Customer Satisfaction in visitors to the Floating Market Lembang tourist area, Bandung, West Java, assisted by the use of Experience Economy. Experience Economy has four variables, that is, Entertainment, Education, Aesthetic, and Escapist all of which are important to map customers’ tendency to prefer. Research utilizes a type of quantitative research that is descriptive. The data was supported through distribution of questionnaires to respondents with a total of 201. This study utilized statistical methods via SmartPLS 3.0. The results of this study show that except for Education, other variables have positive and significant effect on Customer Satisfaction, that is, Entertainment, Aesthetic, and Escapist. Education does not have impact on Customer Satisfaction because it is likely that customers come to Floating Market Lembang to enjoy and relax, not learn, Thus, they do not need much education aspect of this tourism area. Ultimately, Customer Satisfaction gives impact on Customer Loyalty.